Features of Professional and Applied Physical Training of Students - Jaksimbaevich , Utegenov Jalgasbay; Jengisovich, Awezov Islambek (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
The article reveals the content and features of professional and practical training of students of pedagogical specialties in accordance with the requirements of the State Educational Standard of the third generation in practical physical education classes, taking into account the direction and specialty of study at Karakalpak State University.